Qualitative and Quantitative aspects of Pitaya with the use of low doses of a Compound based on Remineralizer and Organic Fertilizer. - Carlesso, L.C.; Lazaroto, R.M.; Lajus, C.R.; Dalcanton, F.; Luz, G.D.; Barrichello, R.; Busnello, F.J.; Moretto, M.A.; Bellé, L.D.A. (International Journal of Advanced Engineering Research and Science, 2020)
The validation of the compost developed based on organic fertilizer and remineralizer makes it possible to add value for both organic fertilizers and crushing companies. The use of national raw material and the potential for demands for organic products, with low cost due to the use of industrial waste, contributing to the environment in the reduction of contaminants and sustainable management. Given the above, the work aimed to characterize and evaluate the viability of Pitaya with the use of low doses of a remineralizer compound and organic fertilizer. The research was developed and applied to a rural property located in the Alto da Serra district, Chapecó-SC. The experiment was conducted with Pitaya, in a randomized block design (DBC), 3 replications and 7 treatments. The plots were distributed by lot, totaling 21 plots, the plants were fertilized with compost based on organic fertilizer and remineralizer. The treatments have the following compositions: T1-0% control (without fertilization); T2-100% remineralizer (2kg); T3-100% organic fertilizer (2kg); T4-50% remineralizer (1kg) + 50% organic fertilizer (1kg); T5-25% remineralizer (0.5kg) + 75% organic fertilizer (1.5kg); T6-75% remineralizer (1.5kg) + 25% organic fertilizer (0.5kg) and T7-poultry litter (2kg). The collected data were submitted to Analysis of Variance by the F Test and the differences between the means were compared by the Tukey Test (p≤0.05). The use of the soil remineralizer with the fertilizer provides increased productivity and fruit revenge, with 2 T / ha being more productive. The treatment with the compost with 50% organic fertilier and 50% remineralizer obtained the highest number of flowers and fruits per plot, highest productivity and the highest financial return, and already in the second year of implantation, the first crop of the crop is paid for. all production and investment costs, showing technically feasible. The treatments do not influence the physical and chemical characteristics of Pitaya fruits. The culture of Pitaya managed with low doses of the compost presents technical and economic viability and shows a promising fruit due to its rusticity, productivity and functional and nutraceutical properties.